Influences of high temperature on mechanical properties of fly ash based geopolymer mortars reinforced with PVA fiber - Kaya, Mehmet; Köksal, Fuat (Revista de la Construcción. Journal of Construction, 2021)
In this study, a geopolymer composite containing PVA fiber was produced to recycle waste fly ash and obtain an eco-friendly binder. Mechanical properties of geopolymer mortars, produced by using F class fly ash which was activated with NaOH (sodium hydroxide), and reinforced by PVA (polyvinyl alcohol) fiber were investigated after high temperature effect. Geopolymer mortar samples produced by mixing with fly ash, sand, water and NaOH were placed in standard molds of 40×40×160 mm3. PVA fibers were used at percentages of 0,5%, 1% and 1,5% by volume in the experiment. Tests were performed on mortars exposed to high temperatures of 200°C, 400°C, 600°C and 800°C for physical and mechanical properties. For the specimens not subjected to high temperatures, an increase in the compressive strength of mortars containing PVA fibers was observed in comparison to mortar without PVA fiber. On the other hand, it was concluded that losses in compressive strength were less for mortar without PVA fiber when compared with the mortars containing PVA fibers. As a result of the modeling, the PVA ratio, which gives the optimum flexural and compressive strength, was determined as 1,47%. As a result of melting of PVA fibers under the effect of high temperature, 83,58% loss of compressive strength was determined in samples containing 1,5% PVA after 800ºC temperature.